Factors Causing the Failure of Indonesia-Singapore Cooperation in Handling Transboundary Haze Pollution - Fadilah, Farhan; Lumban Tobing, Fredy Buhama (Universitas Medan Area, 2025)
Transboundary haze pollution has become an urgent environmental issue in Southeast Asia. As a regional organization in Southeast Asia, ASEAN issued the ASEAN Agreements on Transboundary Haze Pollution (AATHP) international agreement to handle this Issue together. AATHP will act as a regime that makes collaborating easier to handle this Issue. Indonesia and Singapore are two countries that have a high interest in establishing cooperation because of their position as the two most affected countries. However, even with AATHP making cooperation mandatory, Indonesia is still reluctant and uncooperative in collaborating with Singapore. This research will explain why Indonesia took this stance using Oran R. Young's Theory of the Effectiveness of International Environmental Regimes. This research uses qualitative research methods with secondary data sources originating from reports from both countries, books, journal articles, and online media reports. This research found that Indonesia's uncooperative nature was due to differences in approaches between the two countries in dealing with this Issue. On the one hand, Singapore wants to push for a shift amongst ASEAN countries from slash-and-burn practices to a zero-burning policy as an environmentally friendly approach to opening oil palm plantations. However, factors still force Indonesia to allow slash-and-burn practices to continue in its territory. This research also found that the dispute between Indonesia and Singapore on this Issue has caused tensions that extend to the bilateral relations between the two countries, especially regarding whether or not there has been an encroachment of sovereignty based on the actions taken in dealing with transboundary haze pollution. This research recommends that Indonesia and Singapore explore cooperation in technology transfer with minimal potential for sovereignty encroachment and explore compliance mechanism options based on the principle of non-intervention at the ASEAN level.